2010
DOI: 10.2109/jcersj2.118.387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of natural superlattice structure in the binary ZnO&ndash;Fe<sub>2</sub>O<sub>3</sub> system by microwave irradiation

Abstract: Homologous compounds, Fe 2 O 3 (ZnO) m , with the modulated natural superlattice structure were obtained within a short period by solid state reaction of component oxides under 2.45 GHz microwave irradiation. TEM observation revealed that two types of superlattice structures were observed in different Fe concentration; one is longitudinal superlattice structure in a rod shaped precipitation at high Fe concentration, and the other is modulated structure showing zigzag shape at low Fe concentration. It is conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The existence of satellite spots indicated that the rod has a modulated wurtzite-type structure. These results are consistent with an existing study [18]. The TEM observations confirmed that the rod-shaped structure consisted of homologous compounds, Fe 2 O 3 (ZnO) m , and the wurtzite-type phase observed in the XRD pattern corresponded to these homologous compounds.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The existence of satellite spots indicated that the rod has a modulated wurtzite-type structure. These results are consistent with an existing study [18]. The TEM observations confirmed that the rod-shaped structure consisted of homologous compounds, Fe 2 O 3 (ZnO) m , and the wurtzite-type phase observed in the XRD pattern corresponded to these homologous compounds.…”
Section: Resultssupporting
confidence: 92%
“…6a), revealed a zigzag shape in each layer. The zigzag structure of Fe 2 O 3 (ZnO) m was similar to the structure observed in previous studies [16,18]. It is known that the appearance of the zigzag structure is related to the value of m, i.e., the Fe/Zn ratio [34].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In the 1990s, it began to be reported that microwave processes differ from processes that do not use microwaves. For example, microwaves can create supersaturated solid solutions, enhancement of sintering, changes in the materials structure, and so on [6][7][8]. These phenomena are well known as "microwave effects.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we also observed a formation of natural superlattice structure of Fe 2 O 3 (ZnO) m homologous compounds. 58) Important fact is that these materials were synthesized by a simple procedure, only MW irradiation to the powder mixture of ZnO and £-Fe 2 O 3 , suggesting the following mechanism of the reaction. When MWs are irradiated to the powder mixture, rapid heating is achieved by strong coupling with MW energy.…”
Section: Rapid Formation and Decomposition Of Supersaturated Solid Somentioning
confidence: 99%